Consulting Report - Municipality of Surco: Safety and Well–Being - Li, Yihan (2024)
This paper aims to address the issue of community safety in Santiago de Surco, where current security measures fail to meet the needs of the district's residents. Despite the introduction of the Alerta Surco App by the municipality, its limited adoption, functionality, and effectiveness hinder its ability to address safety concerns and foster community engagement. Key challenges include a prevalent sense of insecurity, inefficient communication between residents and authorities, and low awareness of available safety tools. The proposed solution focuses on advancing the Alerta Surco App through the integration of more advanced features, such as chatbots, to promote community engagement in safety issues, provide real-time assistance, and streamline emergency reporting. Meanwhile, a targeted promotion and education campaign aims to increase user adoption and broader community engagement. The solution offers both immediate benefits, by improving communication and response times, and long-term social value, by fostering trust and collaboration between citizens and authorities. The expected impact of implementing these solutions includes improved public safety, a reduction in crime rates, and enhanced community well-being. Financially, the App's advancement would be supported by advertising income and partnerships, and given its scalability, it allows for expansion without substantial additional costs, making it a sustainable solution for long-term growth. By aligning with the Sustainable Development Goals (SDGs), this solution not only addresses short-term security issues but also contributes to broader social sustainability, making the Alerta Surco App a viable, scalable solution for public safety management.